Strategies of Small Traders Facing Modern Minimarkets In Pontianak City - Khosiati, Risky; Syafira, Eka (Universitas Muhammadiyah Pontianak, 2024)
The purpose of this study is to identify the strategies used by small traders when competing with contemporary minimarkets in Pontianak City. This study uses a descriptive qualitative approach by collecting data through observation, documentation, and in-depth interviews with 10 small traders who have been operating for at least 3 years. The results of the study show that the presence of minimarkets has different effects on small traders. Grocery traders have experienced a 30-40% decline in turnover, while fresh produce traders have remained stable. Small traders have strong social relationships, personalized service, and transaction flexibility that modern minimarkets cannot match. The long-term survival strategies implemented include payment flexibility, personalized service, and the use of simple technology such as WhatsApp.